Circulação hidrodinâmica e renovação das águas no complexo estuarino lagunar Mundaú-Manguaba para diferentes configurações de embocaduras - Pinheiro, Mariana Kummer da Rocha (2020)
The Mundaú-Manguaba Estuarine-Lagoon Complex (MMELC) is a system formed by two lagoons, Mundaú and Manguaba, which are connected through narrow channels and share an ocean inlet that shifts positions dynamically. Despite the great socioeconomic significance for the state of Alagoas, the complex has an accelerated process of environmental degradation due to anthropic practices such as the discharge of sanitary sewage, industrial effluents and exploitation of natural resources. Therefore, the aim of this study is to evaluate the hydrodynamic circulation and the water renewal of the lagoon complex, considering the morphological changes occurred in the ocean inlet. The hydrodynamic modeling and the analysis of characteristic hydraulic times were performed with the Hydrodynamic Environmental System (SisBaHiA®) for three scenarios of different inlet configurations (2006, 2014 and 2017). The simulations were carried out using the average freshwater discharge and wind data for dry and wet seasons. The hydrodynamic results indicated higher velocities and tidal ranges at the inlets of the main channels of the Mundaú and Manguaba lagoons. The tidal range revealed that the channel system is an efficient filter in reducing tidal variability inside the lagoons. The residence time indicated possible stagnation areas in the northern region of the Manguaba lagoon and in the eastern and southern portions of the Mundaú lagoon. The residence time, water age and renewal rate simulations showed that MMELC is strongly influenced by the river discharge of the Paraíba do Meio and Mundaú rivers. The scenario with the 2014 configuration had higher renewal rates and, consequently, lower water ages, indicating that the different inlet configurations significantly interfere with the hydrodynamic circulation and water renewal of the lagoon estuarine complex.